Managerial Ability, Income Smoothing, and Firm Value: The Moderating Role of Information Asymmetry - Dina Hidayat; Dodi Okri Handoko; Sandy Moya (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study examines the effect of managerial ability and income smoothing on firm value, with information asymmetry as a moderating variable. Using secondary data from the annual reports of companies in the consumer non-cyclical and consumer cyclical sectors listed on the Indonesia Stock Exchange (IDX) for 2021-2023, the study analyzed 192 observations. Panel data regression was applied with firm value (Tobin's Q) as the dependent variable, while managerial ability, income smoothing, as the independent variables and information asymmetry as the moderating variables. ROA and firm size were used as control variables. The results indicate that neither managerial ability nor income smoothing has a direct significant effect on firm value. However, information asymmetry positively affects firm value and significantly moderates the relationship between managerial ability and firm value in a negative direction. These findings suggest that transparency and information quality are crucial in enhancing the effectiveness of managerial strategies on firm value.